2012
DOI: 10.1016/j.jccw.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Impair Wound Healing

Abstract: The body's response to tissue injury in a healthy individual is an intricate, sequential physiologic process that results in timely healing with full re-epithelialization, resolution of drainage, and return of function to the affected tissue. Chronic wounds, however, do not follow this sequence of events and can challenge the most experienced clinician if the underlying factors that are impairing wound healing are not identified. The purpose of this article is to present recent information about factors that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
180
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 47 publications
2
180
0
4
Order By: Relevance
“…The above facts prove that the course of treatment is directly associated with the level of LBM loss. 1,6,7 Clinical situations which should be taken into account when assessing the risks for developing malnutrition includes: catabolic stress in response to injuries, surgical procedures, wounds, infections, chronic diseases, non-healing open wounds, intestinal fistulae, gastrointestinal tract insufficiency with malabsorption. 1 In this case one of the mistakes in treating the patient was the fact that oral nutrition was introduced too early, with concomitant gastrointestinal tract insufficiency and heavy stoma exudate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above facts prove that the course of treatment is directly associated with the level of LBM loss. 1,6,7 Clinical situations which should be taken into account when assessing the risks for developing malnutrition includes: catabolic stress in response to injuries, surgical procedures, wounds, infections, chronic diseases, non-healing open wounds, intestinal fistulae, gastrointestinal tract insufficiency with malabsorption. 1 In this case one of the mistakes in treating the patient was the fact that oral nutrition was introduced too early, with concomitant gastrointestinal tract insufficiency and heavy stoma exudate.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Due to the above-mentioned reasons, nutrition and the patient's nutritional status are of utmost importance for the initiation of proper healing processes and tissue regeneration. 6 The aim of this work is to present how nutrition and nutritional state influences wound healing processes. The patient in whom the appropriate nutritional management was not implemented, in spite of a very intense surgical treatment, with numerous reoperations developed extreme cachexia with the arrest of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…The available data suggest that the time of bevacizumab administration is crucial to avoid wound healing complications. The surgery should be performed 6-8 weeks after bevacizumab treatment, and this chemotherapeutic should not be taken for at least 28 days after surgery [31,32].…”
Section: The Impact Of Targeted Therapies On Skinmentioning
confidence: 99%
“…The overarching goals of the International Society of Pediatric Wound Care (ISPeW) are to (1) set global standards for the assessment and treatment of pediatric wounds of varying etiologies; (2) provide a forum for international interprofessional collaboration among healthcare professionals, researchers, educators, and industry leaders dedicated to the care of pediatric wounds; (3) promote and support clinical research focused on the prevention, assessment, and treatment of pediatric wounds; (4) collaborate with wound care organizations worldwide on pediatric wound care issues; and (5) provide evidencebased pediatric wound care education to healthcare professionals, parents, and lay caregivers. This edition of Advances in Wound Care includes some of the work that was presented at the 2014 ISPeW meeting in Rome.…”
mentioning
confidence: 99%
“…In addition, there is a growing epidemic of adulttype diseases in children, such as obesity and diabetes, which can impact wound repair. [1][2][3] Furthermore, there are more drug-resistant bacteria and an increased prevalence of methicillin-resistant staphylococcus aureus (MRSA) colonization, which can lead to a challenging community microbial profile that, in turn, leads to more wound infections. [4][5][6][7] A recent study using the NSQIP database demonstrated an increase in the surgical site infection rate in neonates, at 3%, compared to an overall rate of 1.8% in the general pediatric surgery population.…”
mentioning
confidence: 99%